1997
DOI: 10.1002/hep.510260606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of lactulose in cirrhotic patients with and without subclinical hepatic encephalopathy

Abstract: Seventy-five cirrhotic patients with hyperammonemia in ing number of patients with compensated or noncompenthe past or at the time of the study were randomly divided sated cirrhosis are managed in outpatient clinics over a long into two groups (treated with lactulose or nontreated) in 14 period. In these patients, prevention of the above complicahospitals in Japan. Thirty-six cirrhotic patients were diag-tions is necessary in long-term home care to improve the nosed as having subclinical hepatic encephalopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 0 publications
2
103
0
3
Order By: Relevance
“…On the basis of the results of 3 previous published studies, including one of ours, we estimated an average improvement of 15% in MHE in the control group and an average improvement of 75% in MHE in the treatment group. 21,22,35 Our previous data shows that the prevalence of MHE was 62.4% and 65% and that approximately 15% patients were lost to follow-up. 9,22 Therefore, approximately 26 patients were required in each arm, and it was necessary to enroll a total of 80-90 patients with cirrhosis in order to have the desired number of patients in each arm.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the basis of the results of 3 previous published studies, including one of ours, we estimated an average improvement of 15% in MHE in the control group and an average improvement of 75% in MHE in the treatment group. 21,22,35 Our previous data shows that the prevalence of MHE was 62.4% and 65% and that approximately 15% patients were lost to follow-up. 9,22 Therefore, approximately 26 patients were required in each arm, and it was necessary to enroll a total of 80-90 patients with cirrhosis in order to have the desired number of patients in each arm.…”
Section: Methodsmentioning
confidence: 96%
“…[15][16][17] Therapeutic interventions that aim to reduce ammonia are also useful in this setting. [18][19][20][21][22][23][24] Most studies have shown improvement in psychomotor functions coupled with a reduction in ammonia level. Improvement in cognitive functions may translate into improvement in HRQOL.…”
mentioning
confidence: 99%
“…Therefore, lactulose was deemed to be effective in the primary prevention of overt hepatic encephalopathy. 25 Congruent with prior results, several other studies have reported an improvement in neuropsychometric tests with various doses and durations of lactulose and lactitol treatment [25][26][27][28][29][30] (Table 1).…”
mentioning
confidence: 68%
“…25,28,33,34 In a trial of 128 cirrhotic patients, Kalaitzakis et al reported that daily lactulose had a negative impact on HRQoL. 35 The laxative effect and titration to 2-3 soft bowel movements per day make adherence to lactulose classically low.…”
mentioning
confidence: 99%
“…5 6 20-23 30 36 39 Lactulose or lactitol v placebo or no intervention Ten trials with 280 patients (75% men) assessed lactulose or lactitol versus placebo or no intervention (table 1). [20][21][22][23][24][25][26][27][28][29] All patients had cirrhosis and acute, 25 chronic, 20 22-24 acute or chronic, 21 or minimal hepatic encephalopathy. [26][27][28][29] Eight trials assessed oral lactulose, 20-24 26 28 29 one assessed oral lactitol, 27 and one assessed lactitol enemas.…”
Section: Resultsmentioning
confidence: 99%